The reconstruction of palupuh: The story of the natuurmonument and defense base in 1948 - Fikrul Hanif Sufyan; Destel Meri; Nahdatul Hazmi; Y Yuhardi; Aldi Saputra (AGASTYA: JURNAL SEJARAH DAN PEMBELAJARANNYA, 2023)
Palupuh had an important role in the past. Because the area, which was part of the Oud Agam Sumatra Westkust during the Dutch colonial era, was once designated by the government as a natuurmonument or forest conservation area. During the emergency government of the Indonesian republic (PDRI), it was once an important part of the defense of the mobilie brigade or mobbrig, and the ranks of the people from the onslaught of the Dutch army. In principle, this article aims to explain how Palupuh was before independence and the importance of this area for the defense base in 1948-1949. This article is organized in accordance with historical methods, namely heuristics, criticism, interpretation and historiography. The research findings show that during 1948-1949, when the Dutch bombarded Bukittinggi, the mobilie brigade moved its defense base several times. The final choice was Palupuh, which was a defense base in protecting Pasaman, which is in the north and Luhak Limopuluah Koto in the south. The mobrig troops and the nagari or kota defense line (BPNK) heroically guarded the defense bases to the north and south.